How do you solve #4t + 1/3 = t + 5/6 + t - 3/6#?

1 Answer
Apr 15, 2016

Answer:

# t = 0 #

Explanation:

#color(blue)(4t) + 1 /3 =color(blue)(t) + 5/6 +color(blue)(t) - 3/6#

#color(blue)(4t - t -t )= 5/6 - 3/6 - 1 /3 #

#color(blue)(4t - 2t )= 5/6 - 3/6 - 1 /3 #

# 2t = 5/6 - 3/6 - 1 /3 #

The L.C.M of the denominators #( 6 ,6 # and #3)# of the L.H.S #=6#

# 2t = 5/6 - 3/6 - (1 *2 ) /(3 *2 ) #

# 2t = 5/6 - 3/6 - (2 ) /(6 ) #

# 2t = (5 -3 -2 ) /6 #

# 2t = (5 -5 ) /6 #

# 2t = (0) /6 #

# 2t = 0 #

# t = 0 / 2 #

# t = 0 #